Começar de novo: práticas de socialização do professor em início de carreira - Ferreirinho, Viviane Canecchio (2004)
This thesis describes a research carried out in 2003, in a public school (a school supported by the local government) in the city of São Paulo, Brazil, where six teachers were entitled to start their careers through public exam The current study investigated some subjects, such as: how the teachers' socialization process is formed; what practices they face that will guide their lives Into the institution; how they select the learning of these practices, and how they are building professionalism concerning their colleagues during professional life. The analysis was done highlighting four key points: the change in the functional situation; the choice process in the entering school: the periods and classes distribution and the relationship with the technical staff and colleagues. These key points were identified by collected data through environment observation, as well interviews with the teachers. These data have shown essential to understand the socialization process, which is based on a structure of actions and practices. The key points comprehension was supported by Pierre Bourdieu's theory, mainly bis concepts of habitus and campo, which consider career socialization as a professional habitus incorporation, and also the concept of school culture, supported by Vinao Frago e Dominique Julia. The main results obtained concern the frequent disruptions that occur in the teachers' professionalism process, the importance of entering with a position through public exam, a possible future financial stability, the rewarding colleagues' recognition and finally, some hope to finish struggle with some restarting feeling that every teacher in an unstable situation on carrier does